The effects of seed priming on improvement of cold tolerance in germination stage of some in pea genotypes. - mohammad mohammadi; Reza Tavakkol Afshari; Jafar Nabati; Ehsan Oskoueian (علوم و فناوری بذر ایران)
Identification of primings that induce secondary metabolites in order to withstand cold stress can be effective in the establishment and yield of crops. This experiment was conducted in the laboratory conditions as a completely randomized design with three replications to evaluate the effect of seed priming on cold tolerace of three genotypes and one cultivar of chickpea during germination stage in 2020. Treatments include temperatures of 5, 10, 15 and 20 ° C, genotypes of MCC505, ILC8617, MCC495 and Saral cultivar and primings included control (non-primed), hydropriming, sodium chloride, acid salicylic, sodium nitroprusside, phosphorus and potassium soluble bacteria, Full spectrum of 20 essential amino acids, potassium nitrate, zinc sulfate. Results indicated that the treatments of sodium nitroprusside, hydropriming, acid salicylic and zinc sulfate prevented the germination activity from stopping due to the decrease in temperature and among them, sodium nitroprusside treatment was able to improve germination percentage, germination rate, hydrogen peroxide and catalase under 5 ° C compared to the control by 5.7, 19, 4 and 15%, respectively. In addition, the above treatmens under 20 ° C resulted in 2 and 4.7% improvement in alpha-amylase and hydrogen peroxide, respectively. Generally, the effect of priming on cold tolerance at the germination stage showed that cold stress reduces seed germination and germination rate and has a negative effect on germination indices, enzymatic and biochemical activity. However, the use of primings, especially sodium nitroprusside, moderated the effect of cold stress and improved seed characteristics under cold stress.